2016
DOI: 10.1109/tgrs.2016.2547389
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregation of Remotely Sensed Soil Moisture in Heterogeneous Landscapes Using Holistic Structure-Based Models

Abstract: In this study, a novel machine learning algorithm is presented for disaggregation of satellite soil moisture (SM) based on self-regularized regressive models (SRRM) using high-resolution correlated information from auxiliary sources. It includes regularized clustering that assigns soft memberships to each pixel at fine-scale followed by a kernel regression that computes the value of the desired variable at all pixels. Coarse-scale remotely sensed SM were disaggregated from 10km to 1km using land cover, precipi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The accuracy of downscaled soil moisture product in this study appears to be very good as compared to, for example, Mishra et al (), who reported the CONUS average correlation between the thermal‐infrared downscaled SMAP (passive) and SCAN is around 0.54, while in this study, the correlation between the downscaled SMAP product and SCAN networks is 0.65. However, it is noted that the successful use of a downscaling approach may be restricted to its certain characteristics and needs of a user, knowing that each method may have certain strengths and weaknesses (Chakrabarti et al, , ; Chakrabarti, Judge, et al, ; Colliander, Fisher, et al, ). For example, in the work by Colliander, Fisher, et al (), the authors proposed a disaggregation approach to downscale the SMAP soil moisture over a small domain (including three 36‐km SMAP pixels), where the surface temperature is controlled by soil evaporation, the topographical variation is relatively moderate, and the vegetation density is relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of downscaled soil moisture product in this study appears to be very good as compared to, for example, Mishra et al (), who reported the CONUS average correlation between the thermal‐infrared downscaled SMAP (passive) and SCAN is around 0.54, while in this study, the correlation between the downscaled SMAP product and SCAN networks is 0.65. However, it is noted that the successful use of a downscaling approach may be restricted to its certain characteristics and needs of a user, knowing that each method may have certain strengths and weaknesses (Chakrabarti et al, , ; Chakrabarti, Judge, et al, ; Colliander, Fisher, et al, ). For example, in the work by Colliander, Fisher, et al (), the authors proposed a disaggregation approach to downscale the SMAP soil moisture over a small domain (including three 36‐km SMAP pixels), where the surface temperature is controlled by soil evaporation, the topographical variation is relatively moderate, and the vegetation density is relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have used this approach to develop soil moisture at fine spatial scales (Chakrabarti et al, 2016(Chakrabarti et al, , 2017Mascaro et al, 2011;Piles et al, 2011Piles et al, , 2014Srivastava et al, 2013;Verhoest et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A novel machine-learning algorithm is proposed to disaggregate coarse-scale remotely-sensed observations to finer scales, using correlated auxiliary data at the fine scale [130]. The approach includes a regularized Cauchy-Schwarz distance to cluster data and to assign soft memberships to each pixel at the fine scale.…”
Section: Machine Learning Methodologies For Soil Moisture Retrievalmentioning
confidence: 99%